2002
DOI: 10.1089/10430340252792495
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronidase Increases Electrogene Transfer Efficiency in Skeletal Muscle

Abstract: Electrogene transfer (EGT) of plasmid DNA into skeletal muscle is a promising strategy for the treatment of muscle disorders and for the systemic secretion of therapeutic proteins. We report here that preinjecting hyaluronidase (HYAse) significantly increases the gene transfer efficiency of muscle EGT. Three constructs encoding mouse erythropoietin (pCMV/mEPO), secreted alkaline phosphatase (pCMV/SeAP), and luciferase (pGGluc) were electroinjected intramuscularly in BALB/c mice and rabbits with and without HYA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
3

Year Published

2002
2002
2005
2005

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 51 publications
(59 reference statements)
5
67
0
3
Order By: Relevance
“…It has previously been demonstrated that the pretreatment of skeletal muscle with bovine hyaluronidase, prior to plasmid electrotransfer, can significantly improve transfection efficiencies compared to electrotransfer alone, 12,14 and we have previously published data demonstrating that the pretreatment of muscle with hyaluronidase can reduced the damage associated with electrotransfer in nondystrophic muscle. 12 The improvements in transfection efficiency achieved with hyaluronidase and electrotransfer may be a result of improved accessibility of the plasmid DNA to the muscle fibre surface.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…It has previously been demonstrated that the pretreatment of skeletal muscle with bovine hyaluronidase, prior to plasmid electrotransfer, can significantly improve transfection efficiencies compared to electrotransfer alone, 12,14 and we have previously published data demonstrating that the pretreatment of muscle with hyaluronidase can reduced the damage associated with electrotransfer in nondystrophic muscle. 12 The improvements in transfection efficiency achieved with hyaluronidase and electrotransfer may be a result of improved accessibility of the plasmid DNA to the muscle fibre surface.…”
Section: Introductionmentioning
confidence: 88%
“…This difference in the method of entry of plasmid into muscle fibres may explain why hyaluronidase pretreatment improves electrotransfer, but not the direct injection, of plasmid DNA. 12,14 We speculate that the hyaluronidase pretreatment permeabilises the pericellular matrix of the muscle fibre, thus increasing the effective concentration of plasmid at the membrane leading to increased uptake.…”
Section: Plasmid Gene Transfermentioning
confidence: 98%
See 1 more Smart Citation
“…A total of 90 units of type VI-S hyaluronidase from bovine testes (Sigma, St. Louis, MO, USA) were resuspended in 50 ml of sterile saline solution and injected 10 min prior to electroporation as previously described. 42 Commercially available caliper electrodes (model 383, BTX, San Diego, CA, USA) were used for electroporation. The caliper electrodes were applied to the shaved skin on either side of the marked DNA injection point, and the calipers were closed to a gap of 5 mm, so that electrical contact with the skin was maximized.…”
Section: Intramuscular Dna Injection and Electroporationmentioning
confidence: 99%
“…O pré-tratamento com hialuronidase, anterior a injeção de plasmídeo, pode aumentar significativamente a eficiência de transferência gênica, comparado a eletroporação sozinha (MCMAHON et al, 2001); (MENNUNI et al, 2002). Tem sido relatado um aumento de eficiência de transferência gênica, com valores próximos de 10% (VICAT et al, 2000) a 37% (VILQUIN et al, 2001) e até 50% em musculatura não distrófica, associando o tratamento prévio de hialuronidase ao método de eletroporação (GOLLINS et al, 2003); (MCMAHON et al, 2001).…”
Section: O Uso Da Hialuronidase Com Eletroporaçãounclassified